Part-of-speech for old Malay manuscript corpus: A review - Abu Bakar, Juhaida; Omar, Khairuddin; Nasrudin, Mohammad Faidzul; Murah, Mohd Zamri (Springer Berlin Heidelberg, 2013)
Research in Malay Part-of-Speech (POS) has increased considerably in the past few years.From the literature, POS are known as the first stage in automated text analysis and the development of language technologies can scarcely begun without this initial phase.Malay language can be written in Roman or Jawi.Three different spelling between Roman and Jawi make this study essential.In this paper, we highlighted the problem and issues related to Malay language, POS general framework, POS approaches and techniques.POS at basis was introduced to get information from Old Malay Manuscripts that contain important information in various spheres of knowledge.Promising result for the auto-tagging of Malay written in Jawi is expected.